Prophetic Supplications and Economic Stability: A Ḥadīth-Based Analysis through al-Shāṭibī’s Maqāṣid al-Sharīʿah Framework - Muhammad fahrurrozi; Marwan Mas’ud; Zaid Raihan; Dimas Hutomo Putra; Teguh Dwi Prayoga (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the role of duʾāʾ maʾthūr as a spiritual instrument that contributes to economic stability and social well-being through the perspective of ḥadīth and Maqāṣid al-Sharīʿah. Theoretical framework: The theoretical framework uses Critical Discourse Analysis (CDA) and Maqāṣid al-Sharīʿah al-Syāṭibī theory to understand the normative meaning and purpose of sharia in prayer. Literature review: A literature review examines the concept of duʾāʾ maʾthūr, al-Syāṭibī's thought, and Islamic economic ethics that emphasize character formation and social responsibility. Methods: This research is qualitative with the library research method, using secondary data that are analyzed descriptively and deductively. Results: The results of the study show that duʾāʾ maʾthūr has strategic significance in building holistic economic stability. From the perspective of the ḥadīth, the prayer emphasizes the interconnectedness of the spiritual, moral, psychological, and social dimensions, including the plea for protection from poverty, deprivation, and humiliation. From the perspective of al-Syāṭibī, the prayer functions as a normative wasāʾil that harmonizes human efforts with tawakkul, directs the search for sustenance to the halal aspect, and strengthens individual responsibility in the management of wealth. Thus, prayer plays a role as a preventive instrument against economic damage and social dependence. Implications: Prayer is understood as a preventive and transformative instrument in building an ethical, stable, and sustainable economy. Novelty: The novelty of the research lies in the integration of CDA and Maqāṣid al-Sharīʿah in positioning prayer as an economic normative instrument, rather than simply a spiritual practice.